Implicações da pandemia de COVID-19 nas condições e nos modos de cuidado ofertados na primeira infância - Silva, Jordan Prazeres Freitas da (2020)
Introduction: Due to the high incidence rate of COVID-19 in the world, countries have invested in interventions to contain the disease based on physical distance, and this is being able to transform the daily lives of families. Objective: To understand the implications of COVID-19 on the conditions and modes of care offered in early childhood, from the accounts of mothers who were living with this pandemic in Fortaleza, Ceará. Method: A qualitative approach study, outlined by the Oral Stories of Life, which sought to listen to the narratives of mothers who had children in Early Childhood (0 - 6 years) and who experienced the measures to confront and contain the human infection caused by the new coronavirus in Fortaleza, Ceará. For the data collection procedures, we used the semi-structured interview as a tool and for the processing of the empirical material, we used the Bardin Content Analysis as a lens. Results: We interviewed 30 mothers who reported having from one to three born children. The average age among the women was 32 years. Regarding the marital status of the participants, most of them (twenty-seven) were married or cohabiting in a stable union, two were single and one was a widow. The interviewees were grouped by social stratum, dividing them by the HDI of their neighborhoods, being thirteen residents in territories with low HDI (0.189), and seventeen residents of localities with high HDI (0.953). Of the interviewees, four from the disadvantaged HDI group received some type of social benefit from the government (Bolsa Família or Emergency Aid). Most of the women (seventeen) had a high level of schooling (post-graduation), another six concluded higher education, while the rest (seven), from the low social level group, had only high schooling. From the speeches of these women, two main categories of analysis were observed: perceptions, feelings and strategies of mothers to live with the measures to contain the spread of COVID-19; behaviors of parental care and daily life of children in the home context in the face of the coronavirus pandemic. We noticed that the interviewees have doubts about the public health strategies implemented in the country, however, most of them, despite manifesting a series of negative feelings such as: anxiety, extreme tiredness, stress, irritability, impatience, fear and concern; they have followed the determinations of the health authorities and narrate perceiving the actions to mitigate the disease as safety measures for the population. As a strategy to face the experiences of the pandemic, it was verified that many mothers tried not to think about the disease and used digital technologies as a way to keep the social support network active and feel some relief from the induced physical distance. We also noticed that during the pandemic most of the caregivers of this research were fully responsible for the care of their children and that there was greater participation of men in this process. Another issue highlighted was that part of the families sought ways, mainly playful, to transform the stressful context of the pandemic into a minimally pleasant scenario for children. It was also possible to notice that, despite the insertion of manual activities in the daily lives of families, children spent more time in front of screens and presented changes in behavior, with symptoms of agitation, anxiety, excessive dependence of parents, sleep disorders, stress and fear. Final considerations: In order to be offered favorable conditions for early childhood care, the caregivers need to be minimally healthy. Therefore, it is relevant to perform a medium and long term monitoring of maternal mental health and conditions for the exercise of positive parenting in the post-pandemic. It is necessary to monitor the development of the children at home, as well as their return to face-to-face activities.